Tenascin-W: Discovery, Evolution, and Future Prospects - Degen, Martin; Scherberich, Arnaud; Tucker, Richard P. (Frontiers in Immunology, 2021)
Of the four tenascins found in bony fish and tetrapods, tenascin-W is the least understood. It was first discovered in the zebrafish and later in mouse, where it was mistakenly named tenascin-N. Tenascin-W is expressed primarily in developing and mature bone, in a subset of stem cell niches and in the stroma of many solid tumors. Phylogenetic studies show that it is the most recent tenascin to evolve, appearing first in bony fishes. Its expression in bone and the timing of its evolutionary appearance should direct future studies to its role in bone formation, in stem cell niches, and in the treatment and detection of cancer.